Inovasi Pemanfaatan Limbah Plastik Menjadi Ecobrick dan Barang Fungsional - Sabilah Sabilah; Widianingsih Widianingsih; Vinah Lusianah; Siti Uripah; Lucky Zulkarnaen; Asih Wahyuningsih; Hety Marianah (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
One way to recycle and reuse plastic is using ecobricks. Sustainable bags, wallets, chairs, tables, and more may be yours via the ecobrick program's processing of basic, inexpensive materials. This study seeks to inspire Class 6 students at SDN 1 Sumber to become more involved and think outside the box when it comes to recycling and repurposing materials that have high market value. With a descriptive qualitative approach, this researcher involved grade 6 students and homeroom teachers at SDN 1 Sumber as subjects, using interview, observation and documentation methods. The results of this research show a significant increase in understanding of the use of plastic waste into ecobricks and functional goods after participating in practical ecobrick making activities. So students can gain new insight into plastic waste processing and develop creative ideas. This research provides educational and environmental benefits, this activity also supports the development of student character, such as cooperation, creativity and caring. Key words: ecobricks, waste, plastic.